Html, xhtml, and css bible ebook - Schafer, Steven M. (Bible., 2011)
An essential update to the key web authoring standards of HTML, XHTML, and CSS The existence of Web pages depends on three vital technologies: HTML (base language that Web pages are written in), XHTML (standards that define how to write HTML pages), and CSS (standard that applies formatting styles to Web pages). This new edition provides you with critical coverage of these three Web authoring standards, and places special focus on the upcoming releases of HTML 5 and CSS 3. Serving as a tutorial and reference, this comprehensive resource explains the basic structure and necessary formatting to create a static (non-changing) and dynamic (changing) page on the Internet. HTML, XHTML, and CSS are the three major Web authoring standards for creating either a static or dynamic Web page Guides you through using HTML to create Web documents and introduces updates to HTML 5 Demonstrates best practices for using tools and utilities to create Web documents Includes coverage of the new CSS 3 and tips and tricks for maximizing its abilities Helpful examples round out this essential guide and will get you up and running with HTML, XHMTL, and CSS in no time! Note: CD-ROM/DVD and other supplementary materials are not included as part of eBook file.